The effect of climatic change on the rheological properties of winter wheat doughs - Boros, Norbert; Kónya, Éva; Fórián, Sándor; Győri, Zoltán (Acta Agraria Debreceniensis, 2010)
In present paper we have examined the effect of climatic change on the extensigraph characteristics of wheat-flours. The baking quality of winter wheat is largely determined by cultivar, but it can be influenced by weather conditions during growing period. Flours were from 5 cultivars grown at one location in three cropping years. We have found that the extensigraph properties of dough are affected by the weather conditions, nevertheless, different cultivars distinctly react to the increase of temperature and decrease of precipitation. In generally, the higher average day temperature and lower precipitation level is favourable to produce winter wheat flour with better quality